2009
DOI: 10.1542/peds.2008-2232
|View full text |Cite
|
Sign up to set email alerts
|

A Second Course of Ibuprofen Is Effective in the Closure of a Clinically Significant PDA in ELBW Infants

Abstract: In our study population, PDA closure was gestation dependant, with a cumulative closure rate of 65%. A similar proportion of infants closed their PDA following the first and second courses regardless of gestation. These data suggest that a second course of ibuprofen may be effective in closing a PDA in even the most preterm infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 35 publications
3
37
4
Order By: Relevance
“…The rate of ligation in the present study, in infants receiving more than one course of indomethacin, although higher than reported in recent cohort studies (6,8,(10)(11)(12), was still within the range reported in the literature (4,5,15,17,18). Koehne et al (4) reported an overall ligation rate of 57% and a 34% ligation rate in 101 babies who had indomethacin treatment.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The rate of ligation in the present study, in infants receiving more than one course of indomethacin, although higher than reported in recent cohort studies (6,8,(10)(11)(12), was still within the range reported in the literature (4,5,15,17,18). Koehne et al (4) reported an overall ligation rate of 57% and a 34% ligation rate in 101 babies who had indomethacin treatment.…”
Section: Discussionsupporting
confidence: 61%
“…Other centres continue to perform a comparable number of ligations. A United Kingdom cohort of 172 extremely low birth weight infants with PDA had a 53% ligation rate in infants receiving more than one course of ibuprofen (18). As well, 2009 Vermont-Oxford data showed a mean ligation rate of 21% for all 24 to 26 weeks' gestational age infants.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The incidence of PDA in term infants has been estimated to be 57 per 1,00,000 live births [3], whereas one in every three preterm infant with a birth weight of 501 to 1500 g (very low birth weight [VLBW]) can be expected to have a PDA [4,5], contributing to significant morbidity and mortality in preterm infants. The shunting of blood through a PDA in premature infants is essentially all left-to-right.…”
Section: Introductionmentioning
confidence: 99%
“…Vieux found a significant decrease in glomerular filtration and tubular function impairment in the ibuprofen group that was not seen in the patients who did not receive ibuprofen (30). Richards reported that the effectiveness of ibuprofen in closing a PDA decreased with a second course, and that creatinine was significantly higher in neonates receiving a second course as compared to controls (32).…”
Section: Discussionmentioning
confidence: 97%